Penjadwalan Penggantian Komponen Penggiling Adonan Bakso Kapasitas 5 kg/Jam - Bagus Prabowo; Syamsul Hadi; David Fajar Pratama; Fayshal Amirul Mu’Minin; M. Sofi Alfuadi Arif (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Problems in the meatball dough grinder are low production, increasing maintenance costs and disappointed meatball dough customers who receive orders late due to problems with the electric motor, Pulley, V belt, cutting knife. The purpose of the replacement scheduling is to obtain costs, maintenance-repair schedules in the period 2026, and the ratio of maintenance costs to profits. The replacement scheduling method includes collecting previous period maintenance data, applying the inspection-replace-repair-overhaul (IRRO) method, evaluating component working conditions, predicting component life, predicting repairman costs, predicting supporting equipment that will be used in maintenance, predicting the time to replace spare parts or reinstall components after repair, estimating maintenance and repair costs in 2026, and calculating the ratio of maintenance costs to profits. The results of the replacement scheduling show that the maintenance costs in 2026 are IDR 2,530,000 with an estimated rental rate for the meatball dough grinder of IDR 10,000/kg which has the potential to be rented for 1300 hours/year, and the ratio of maintenance costs to profits is 4.9% which implies that the meatball dough grinder with a capacity of 5 kg/hour still has the potential to sell well and is suitable for use in the coming years.